Exceptional Longevity in Okinawa:: A Plea for In-depth Validation - Michel Poulain (Demographic Research, 2011)
The exceptional longevity in Okinawa has been largely investigated. Such situation should be thoroughly validated both for individual ages and the level of population longevity. This contribution analyzes available demographic data on the population of Okinawa in order to explain the emergence of large numbers of centenarians. The existence of a mortality crossover obtained by comparing mortality rates in Okinawa and Japan could be attributed either to different behaviour between generations born before or after WW II or to bad data. This paper does not favour any of these explanations but pleas for a more in-depth validation of the longevity in Okinawa.